DINAMIKA INDUSTRI RAWAI TUNA DI PELABUHAN BENOA - Fathur Rochman; Irwan Jatmiko; Zulkarnaen Fahmi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2018)
ABSTRACTThis study presents information about the dynamics of industrial scale tuna longline development in Indonesia, especially tuna longline fisheries in the Eastern Indian Ocean. This study uses a descriptive method based on tuna longline enumeration data landed at Benoa port from 2012 to 2015. Benoa is one of the three main fishing ports in Indonesia, besides Nizam Zachman (Jakarta) and Cilacap (Central Java). It contributes the largest number of tuna catches to 60% of the total long-scale tuna catch industry in the Indian Ocean. This makes Benoa as the main barometer of industrial tuna fisheries in Indonesia. Industrial scale of tuna longline fisheries activities have dropped significantly to 76% from 2004 to 2015. Highest decline occurred in 2004 to 2006 by 43% followed by 2009 to 2010 at 41% and 2014 to 2015 at 19%. Enumeration data coverage in Benoa port is about 57% to 64% of total ship landing. Catch dominated by export products followed by local quality and bycatch products. The catch composition is dominated by four tuna species (BET, YFT, SBT and ALB) which reach 88% of the total catch followed by bycatch of 6.23% and fish with beaks of 5.46%. In period 2012 to 2014, fishing efforts are directly proportional to the number of ships and tuna production, but in 2015, capture efforts, CPUE and catch production increased along with the decline in the number of ships operating.Keyword: Benoa Port, enumeration program, tuna longlineABSTRAKStudi ini menyajikan informasi tentang dinamika perkembangan rawai tuna skala industri di Indonesia khususnya perikanan rawai tuna di Samudera Hindia Bagian Timur. Studi ini menggunakan metode deskriptif yang berbasis data enumerasi perikanan rawai tuna yang didaratkan di Pelabuhan Benoa tahun 2012 sampai dengan 2015. Pelabuhan Benoa merupakan satu dari tiga pelabuhan perikanan utama di Indonesia disamping Nizam Zachman (Jakarta) dan Cilacap (Jawa Tengah). Pelabuhan Benoa menyumbangkan jumlah tangkapan ikan tuna terbesar mencapai 60% dari total tangkapan rawai tuna skalaindustri di Samudera Hindia. Hal ini menjadikan Pelabuhan Benoa sebagai barometer utama perikanan tuna skala industri di Indonesia. Kegiatan perikanan rawai tuna skala industri telah menurun secara signifikan hingga 76% dari 2004 sampai 2015. Penurunan tertinggi terjadi pada 2004 sampai 2006 sebesar 43% diikuti 2009 hingga 2010 sebesar 41% dan 2014 sampai 2015 sebesar 19%. Cakupan data enumerasi di Pelabuhan Benoa adalah 57% sampai 64% dari total pendaratan kapal. Hasil tangkapan didominasi oleh produk ekport diikuti oleh produk kualitas lokal dan produk hasil sampingan. Komposisi hasil tangkapan didominasi oleh empat spesies tuna (BET, YFT, SBT dan ALB) yang mencapai 88% dari total tangkapan diikuti oleh hasil tangkapan sampingan sebesar 6,23% dan ikan berparuh sebesar 5,46%. Pada periode 2012 sampai 2014, upaya penangkapan berbanding lurus dengan jumlah kapal dan produksi tuna namun pada tahun 2015 upaya penangkapan, CPUE dan produksi hasil tangkapan meningkat seiring dengan turunnya jumlah kapal yang beroperasi.Kata kunci: Pelabuhan Benoa, program enumerasi, rawai tuna